Teachers' well-being and mental health in Indonesia: Does work-related stress mediate the relationship? - Heleni Filtri; H. Hardi; Nisaul Hasanah (Research and Development in Education (RaDEn), 2025)
The quality of learning in the educational process is determined by the quality of teachers, which is characterized by their psychological well-being. In fact, there is still very little research on teachers' psychological well-being and work stress in Indonesia. This study aims to determine the effect of well-being on mental health, mediated by work stress, among teachers in Indonesia. This study is a cross-sectional study. The study involved 201 teachers of all levels in Indonesia using quota sampling. The data collection techniques for well-being, stress, and mental health, using non-test methods, involved valid and reliable instruments. The research data were analyzed using descriptive quantitative analysis, path analysis, and Sobel's test. The path analysis results show that teacher welfare has a direct effect on teacher stress levels. Furthermore, teacher stress levels have a direct impact on teacher mental health, while the stress scale acts as a mediator in the relationship between welfare and teacher mental health. The findings of this study are expected to form the basis for the development of policies and programs for teachers in Indonesia that are more appropriate for improving the welfare and mental health of teachers and educational standards in Indonesia.